Increasing intranet usage through gamification – Insights from an experiment in the banking industry - Morschheuser, Benedikt; Henzi, Christian; Alt, Rainer (Proceedings of the 48th Hawaii International Conference on System Sciences, 2015)
This paper applies gamification to leverage the use of information for information-intensive business tasks in the context of corporate intranets. It presents the results of an online experiment, which was conducted in the banking industry with 68 advisors from different institutes using a prototype of a corporate intranet. They indicate that adding gamification elements, such as ranking lists and points, positively influences the quantitative (time spent, articles read) and qualitative (time per article, percentage of correct answers) usage of the intranet for knowledge acquisition.
CRIS-Team Scopus Importer:2021-02-01
Keywords: Banking; Context; Prototypes; Games; Business; Knowledge acquisition; Intranets; Information use; Information-intensive business tasks; Corporate intranet usage; Gamification elements; List ranking; Point ranking; Quantitative analysis; Qualitative analysis